Two‐Dimensional Supramolecular Electron Spin Arrays. (22nd January 2013) - Wäckerlin, Christian; Nowakowski, Jan; Liu, Shi‐Xia; Jaggi, Michael; Siewert, Dorota; Girovsky, Jan; Shchyrba, Aneliia; Hählen, Tatjana; Kleibert, Armin; Oppeneer, Peter M.; Nolting, Frithjof; Decurtins, Silvio; et al.
<x xml:space="preserve">Abstract</x> A bottom‐up approach is introduced to fabricate two‐dimensional self‐assembled layers of molecular spin‐systems containing Mn and Fe ions arranged in a chessboard lattice. We demonstrate that the Mn and Fe spin states can be reversibly operated by their selective response to coordination/decoordination of volatile ligands like ammonia (NH3). <boxed-text content-type="graphic" position="anchor" orientation="portrait"> </boxed-text>